Potentials of Utilizing Biodiesel from Cotton Seed Oil Blend with Diesel as an Alternative to Diesel Fuel in Nigeria - Hussain, I. A.; Ibrahim, I. U.; Ishak, B. A.; Ahmed, A. S. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2020)
The depletion of fossil fuel reserves coupled with the environmental challenges pose by fossil fuel utilization make it necessary to search for better alternative fuels that have less adverse impact to the environment. Biodiesel and its blends as an alternative fuel in compression ignition (CI) engines are receiving more attention from researchers. This study investigates a blend of biodiesels from cottonseed oil and pure diesel prepared in percentage by volume in a proportion of 0:100, 10:90, 20:80 and 30:70 respectively. They were labeled as B0, B10, B20, and B30, and run on a single-cylinder, four stroke and water-cooled 165F diesel engine. The results show higher brake power for all blends when compared with pure diesel, with the lowest difference of 0.43% for B10 at a torque of 10 Nm and highest of 2.06% for B30 at 2 Nm torque. Specific fuel consumption (SFC) was also higher for the blends as compared to pure diesel, but the SFC is compensated with higher brake power. Pure diesel is observed to be thermally more efficient than biodiesel blends at low torque. The thermal efficiency difference ranges between 6.6–13.3% at 2 Nm. But at the torque of 10 Nm, the thermal efficiency of all blends is higher than pure diesel with about 3.3%. B30 shows better engine performance than pure diesel and the other two blends, but with slightly higher fuel consumption.